2012
DOI: 10.1590/s2179-83972012000200013
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento endovascular da dissecção crônica de aorta tipo B complicada

Abstract: Background: Endovascular repair of aortic diseases is a well-established therapeutic alternative for patients with the appropriate anatomy and/or high surgical risk, as it provides lower morbidity and mortality rates. This study aimed to analyse the outcomes of asymptomatic patients undergoing endovascular treatment of thoracic aortic dissections with an aortic diameter > 5.5 cm or endoleaks. Technical success, therapeutic success, morbidity, mortality, and perioperative complication and reintervention rates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 22 publications
0
2
0
10
Order By: Relevance
“…The improvement of endovascular techniques and the association to surgical revascularization of the supra-aortic trunks allowed its application in aortic arch diseases, territory in which the conventional surgical treatment can bring high morbimortality rates [ 11 ] . Systematic reviews and recent clinical studies have confirmed the benefits of endovascular method over conventional surgery in this aortic segment [ 1 - 3 , 7 , 11 - 13 ] . A suitable anchoring zone in which there is at least 2 cm of healthy aortic extension is required for proper stent implantation, thereby preventing type I endoleak and maintaining the prosthesis durability for a long period [ 14 ] .…”
Section: Discussionmentioning
confidence: 97%
“…The improvement of endovascular techniques and the association to surgical revascularization of the supra-aortic trunks allowed its application in aortic arch diseases, territory in which the conventional surgical treatment can bring high morbimortality rates [ 11 ] . Systematic reviews and recent clinical studies have confirmed the benefits of endovascular method over conventional surgery in this aortic segment [ 1 - 3 , 7 , 11 - 13 ] . A suitable anchoring zone in which there is at least 2 cm of healthy aortic extension is required for proper stent implantation, thereby preventing type I endoleak and maintaining the prosthesis durability for a long period [ 14 ] .…”
Section: Discussionmentioning
confidence: 97%
“…Digital AG remains as the standard in the investigation of parietal branches such as, for example, the bronchial arteries, intercostal arteries, and those arteries supplying the spinal cord (17)(18)(19)(20) . This has implications for the rate of complications.…”
Section: Discussionmentioning
confidence: 99%
“…Ao oferecer uma gama mais ampla de abordagens terapêuticas, essas técnicas permitem uma personalização ainda maior do tratamento, adaptando-se às necessidades individuais de cada paciente. O desenvolvimento contínuo dessas técnicas, aliado aos avanços tecnológicos, promete continuar a melhorar os resultados e a qualidade de vida dos pacientes com AAA 2,8 .…”
Section: Técnica De Clampagem Transperitoneal Ou Retroperitonealunclassified
“…Os pacientes submetidos ao EVAR geralmente têm um tempo de internação hospitalar mais curto em comparação com a cirurgia aberta, o que reduz os custos hospitalares e o risco de infecções hospitalares. Além disso, devido à natureza minimamente invasiva do procedimento, os pacientes podem retornar às suas atividades normais mais rapidamente após o EVAR, melhorando significativamente a qualidade de vida pós-operatória 3,8 .…”
Section: Reparo Endovascular De Aneurisma De Aorta Abdominal (Evar)unclassified
See 1 more Smart Citation